Los rotarios y la erradicación de la polio en el Perú - Lossio, Jorge (2013)
This paper analyzes the process of the erradication of polio desease in Perú during the period of 1985-1991 following an initiative of the Pan American Health Organization (PAHO) which was financed by the Rotary Club International. Accordingly, this paper shows the problems this organization had to face during those years due to inefficient government apparatus as well as the presence of an internal armed conflict across the country. This situation did not frighten away the Rotarians, who not only aided financially, but also volunteered and personally helped with the "sweep" (mass vaccination) in both, urban and rural areas of Peru.